Antioxidative and antimicrobial edible chitosan films blended with stem, leaf and seed extracts of Pistacia terebinthus for active food packaging. Issue 8 (17th January 2018) - Kaya, Murat; Khadem, Sanaz; Cakmak, Yavuz Selim; Mujtaba, Muhammad; Ilk, Sedef; Akyuz, Lalehan; Salaberria, Asier M.; Labidi, Jalel; Abdulqadir, Ako Hamasaeed; Deligöz, Engin
Abstract : Chitosan films blended with stem, leaf and seed extracts of Pistacia terebinthus for active food packaging. Abstract : Methanol extracts of stem, leaf, and seed obtained from Pistacia terebinthus which are rich in phenolic compounds were used for the first time to produce chitosan-based antioxidative and antimicrobial films. All the produced films were characterized by FT-IR, TGA, DSC, SEM, contact angle measurements, and UV-Vis spectroscopy and mechanically. As was expected, incorporation of the plant extracts into chitosan films enhanced the antioxidant and antimicrobial activities effectively. Also, the elasticity of chitosan-seed and chitosan-stem films was improved. The eco-friendly nature of the produced blend films was determined through soil and water degradation analyses. All these findings lead to the conclusion that the produced blend films with Pistacia terebinthus extracts can be applied as alternative food packaging material.